Relation of quantitative flow ratio with transit time coronary artery bypass graft flow measurement - Chen, Cong; Zhao, Yang; Li, Wei; Zhang, Kui; Dang, Haiming; Liu, Taoshuai; Song, Yue; Zheng, Jubing; Dong, Ran (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background. Quantitative flow ratio (QFR) is a new functional index to assess functional significance of the coronary stenosis. While whether there is association between QFR and transit-time flow measurement (TTFM) parameters of the target coronary artery has not been well addressed. Methods. A total of 89 patients receiving the in-situ left internal thoracic artery (LITA) grafts to the left anterior descending artery (LAD), and 19 patients underwent the saphenous vein grafts (SVG) were enrolled in this retrospective study. The QFR value of the LAD were evaluated preoperatively . According to the QFR values, patients with the LITA to the LAD bypass grafts were divided into two groups (group A1: QFR<0.75, group A2: QFR≥0.75), and SVG patients were divided into two groups (V1 group: QFR<0.75, V2 group: QFR≥0.75). Results. Among patients with LITA in-situ graft to LAD, there were significant differences in mean graft flow(Qm) (P=0.034) and pulsatility index(PI) (P=0.030) of group A1 and A2. And the correlation coefficient between QFR and TTFM parameters was Qm: r= -0.15 (P=0.162), PI: r= 0.265 (P=0.012). Among the young and middle-aged population (age<65 years), the positive correlation between QFR and PI is more significant (P=0.007). While in the SVG group, there is no significant correlation. Conclusion. TTFM variables, especially the PI, are strongly affected by preoperative QFR values, especially in the young and middle-aged population. Moreover, in functionally mild coronary stenosis, the chance of competitive flow increases.